Parameters identification for a model of T cell homeostasis - Houssein Ayoub; Bedreddine Ainseba; Michel Langlais; Rodolphe Thiébaut (Mathematical Biosciences and Engineering)
In this study, we consider a model of T cell homeostasis based on the Smith-Martin model. This nonlinear model is structured by age and CD44 expression. First, we establish the mathematical well-posedness of the model system. Next, we prove the theoretical identifiability regarding the up-regulation of CD44, the proliferation time phase and the rate of entry into division, by using the experimental data. Finally, we compare two versions of the Smith-Martin model and we identify which model fits the experimental data best.